Thalidomide and dexamethasone combination for multiple myleoma refractory to dexamethasonebased regimens - Dimopoulos, M.A.; Zervas, K.; Galani, E.; Grigoraki, V.; Vervessou, E.; Samantas, E.; Kiamouris, C.; Gika, D.; Papadimitriou, C.; Anagnostopoulos, N. (Blood, 2000)
Recent data suggest that thalidomide is active in approximately 30% of patients (pts) with refractory multiple myeloma. Between 7/99 and 7/00 we treated 38 pts with refractory myeloma with thalidomide 200 mg PO q.h.s, increased to 400 mg after two weeks (in absence of severe side effects), and intermittent dexamethasone 40 mg p.o. x 4 days on days 1-4, 9-12, 17-20 followed by monthly dexamethasone (days 1-4). Pts median age was 67 years (49 to 79 years). Immediately prior therapy has consisted of high-dose pulse dexamethasone (21 pts) or VAD (17pts). Twelve pts had previously received an autologous stem cell transplant. Fourteen pts were considered as primary refractory and 24 pts were treated during refractory relapse. Serum b2-microglobulin > 3.0 mg/dl was present in 66% of pts and elevated serum LDH in 26%. Among the 33 patients évaluable for response so far, 17 (52%) have achieved a partial response defined by reductions > 50% of serum monoclonal protein and/or by >75% of urine monoclonal protein. The time to response was short (median: 1.5 months, range 0.5 to 3 months). Side effects included constipation (75%), morning somnolence (54%), tremor (25%), dry skin/rash (18%), headache (14%) and peripheral neuropathy (7%). Our results indicate activity of the combination of thalidomide with dexamethasone in pts with multiple myeloma refractory to dexamethasone-based regimens. Pts accrual and follow up is ongoing in order to define the activity of this combination in pts'subsets and to assess the duration of response.